The mammography and MRI manifestations of adenomyoepithelioma of the breast. Issue 3 (March 2016) - Zhang, L.; Qin, G.; He, Z.; Chen, W.; Yang, L.
Abstract : Aim: To investigate mammography and magnetic resonance imaging (MRI) manifestations of benign and malignant adenomyoepithelioma (AME), in order to improve our understanding of this disease. Materials and methods: Thirteen patients (11 cases of benign AME and two cases of malignant AME) were included. All patients underwent preoperative mammography, and four underwent preoperative MRI examinations. Results: Mammography revealed that 11 cases showed round, lobulate, or oval masses. One case was accompanied by calcification with blurred edges; the remaining 10 cases showed masses with clear or shaded borders. One case exhibited structurally distorted lesions, and another showed focal opacities. Among the four patients who also underwent preoperative MRI examinations, signals in the three benign cases were clearly enhanced homogeneously, and the dynamic enhancement curves were progressive. The one case of malignant AME showed an irregularly shaped mass with spiculate margins on the MRI images. The signals were homogeneously enhanced, and the dynamic enhancement curve was of the washout type. Conclusion: AME usually exhibited oval or round masses with smooth edges and no calcification, and, in a portion of the cases, structurally distorted lesions or focal opacities. On different MRI sequences, AME usually showed homogeneous signal. The apparent diffusion coefficient value of malignant AME is relatively low. Highlights: AME commonly showed round, lobulated or oval masses occasionally accompanied by calcification. Less commonly, AME exhibited structurally distorted lesions or focal opacities. The MRI features are strongly divided between benign AME and malignant AME.